Munni aur nomi - Nishat, naqvi; Anwar Jahan (Book Group; Karachi, 2003)
Munni Aur Nomi is a heartwarming story of two friends, Munni and Nomi, whose adventures teach valuable lessons about friendship, kindness, and the importance of helping others.